background image

Take any subset

S

of

A

. Let

D

be the smallest upper set containing

S

. (It exists because

Up

(

A

)

is closed under arbitrary joins.) This is

D

=

f

x

2

A

j 9

s

2

S

:

x

w

s

g

:

Any lower bound of

D

is clearly an upper bound of

S

since

D

S

. Conversely any lower

bound of

S

is a lower bound of

D

. Thus

S

and

D

have the same set of lower bounds, hence

have the same greatest lower bound.

Proposition 17.

[TODO: Move it above in the book.]

For any poset

A

the following are mutually

reverse order isomorphisms between upper sets

F

(ordered reverse to set-theoretic inclusion) on

A

and order homomorphisms

'

:

A

op

!

2

(here

2

is the partially ordered set of two elements:

0

and

1

where

0

v

1

), dened by the formulas

1.

'

(

a

) =

1

if

a

2

F

0

if

a

2

/

F

for every

a

2

A

;

2.

F

=

'

¡

1

(1)

.

Proof.

Let

X

2

'

¡

1

(1)

and

Y

w

X

. Then

'

(

X

) = 1

and thus

'

(

Y

) = 1

. Thus

'

¡

1

(1)

is a upper set.

It is easy to show that

'

dened by the formula (1) is an order homomorphism

A

op

!

2

whenever

F

is a upper set.

Finally we need to prove that they are mutually inverse. Really: Let

'

be dened by the formula

(1). Then take

F

0

=

'

¡

1

(1)

and dene

'

0

(

a

)

by the formula (1). We have

'

0

(

a

) =

(

1

if

a

2

'

¡

1

(1)

0

if

a

2

/

'

¡

1

(1)

=

1

if

'

(

a

) = 1

0

if

'

(

a

) =

/ 1

=

'

(

a

)

:

Let now

F

be dened by the formula (2). Then take

'

0

(

a

) =

1

if

a

2

F

0

if

a

2

/

F

as dened by the formula

(1) and dene

F

0

=

'

1

(1)

. Then

F

0

=

'

1

(1) =

F :

Lemma 18.

For a complete lattice

A

, the map

d

:

Up

(

A

)

!

A

preserves arbitrary meets.

Proof.

Let

S

2

P

Up

(

A

)

. We have

d

S

2

Up

(

A

)

.

d d

S

=

d d

X

2

S

X

=

d

X

2

S

d

X

is what we needed to prove.

Lemma 19.

A complete lattice

A

is a co-frame i

d

:

Up

(

A

)

!

A

preserves nite joins.

Proof.

)

.

Let

A

be a co-frame. Let

D; D

0

2

Up

(

A

)

. Obviously

d

(

D

t

D

0

)

w

d

D

and

d

(

D

t

D

0

)

w

d

D

0

, so

d

(

D

t

D

0

)

w

d

D

t

d

D

0

.

Also

d

D

t

d

D

0

=

S

D

t

S

D

0

=

(because

A

is a co-frame)

=

S

f

d

t

d

0

j

d

2

D; d

0

2

D

0

g

.

Obviously

d

t

d

0

2

D

\

D

0

, thus

d

D

t

d

D

0

S

(

D

\

D

0

) =

d

(

D

\

D

0

)

that is

d

D

t

d

D

0

w

d

(

D

\

D

0

)

. So

d

(

D

t

D

0

) =

d

D

t

d

D

0

that is

d

:

Up

(

A

)

!

A

preserves

binary joins.

It preserves nullary joins since

d

Up

(

A

)

?

Up

(

A

)

=

d

Up

(

A

)

A

=

?

A

.

3